PENGARUH EARNINGS, OPERATING CASH FLOW DAN ASSET GROWTH TERHADAP STOCK RETURN PERUSAHAAN YANG TERDAFTAR PADA INDEKS LQ 45 UNTUK PERIODE 2009-2011 - Yulius ,; Yuliawati Tan (Media Riset Akuntansi, Auditing & Informasi, 2016)
The objective of this research is to test the impact of earnings, operating cash flow and asset growth to firm’s stock return which listed in LQ 45 index in Indonesian for 2009-2011. The result of this research is earnings, operating cash flow and asset growth have not significant effect to stock return both when those variabels is tested separately or silmutaneously. This result show that earnings, operating cash flow and asset growth are not only the one to be the basis of consideration for investor to make investment to get the stock return. Therefore, for making investment, investor should consider other factors which effect the firm’s stock return as macro economics and politics. Furthermore, from this result, be expected an improvement of quality financial statement which addopted IFRS.Keyword: Earnings, Operating Cash Flow, Asset Growth, Stock Return.